Light non-aqueous phase pollutant self-recognition slow-release repair material as well as preparation method and application thereof

By adopting a multi-layer core-shell structure, the lightweight non-aqueous phase pollutant self-identification sustained release repair material, and using its self-identification and sustained release functions, the problems of tail rebound, low effective utilization and low recognition in the treatment of LNAPL phase pollutants in the prior art are solved, and efficient pollutant removal and utilization are achieved.

CN119858970APending Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202311370394.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art has problems such as tail rebound, low effective utilization rate and low recognition when dealing with light non-aqueous phase pollutants, making it difficult to efficiently remove LNAPL phase pollutants.

Method used

A lightweight non-aqueous phase contaminant self-identification sustained release repair material using a multi-layer core-shell structure consisting of a core, a first coating layer and a second coating layer. The core contains an oxidative repair agent, the first coating layer consists of a thermosetting resin, has a pore structure to control the release rate of the agent, and the second coating layer contains a fat-soluble material that can be self-identified and dissolved to initiate the release of the repair agent.

Benefits of technology

The selective identification and efficient removal of LNAPL phase pollutants is achieved, which avoids the consumption of repair materials by soil and groundwater, improves the utilization rate of agents, and solves the problem of tailing rebound.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858970A_ABST
    Figure CN119858970A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of site pollutant remediation, in particular to a light non-aqueous phase pollutant self-recognition slow-release remediation material and a preparation method and application thereof. The light non-aqueous phase pollutant self-recognition slow-release repair material is of a multi-core-shell structure, and the multi-core-shell structure is provided with an inner core, a first coating layer and a second coating layer which are sequentially distributed from inside to outside; wherein the inner core contains a repairing component; the first coating layer is provided with holes, and the first coating layer contains thermosetting resin; the second coating layer contains a fat-soluble material. The self-recognition slow-release repair material for the light non-aqueous phase pollutants has a selective recognition function for the LNAPL phase pollutants, and the second coating layer can be self-dissolved when encountering the LNAPL phase pollutants or high-concentration oil in water, so that release of an LNAPL phase pollutant repair medicament material is started, and timely and efficient purification and removal of the LNAPL phase pollutants are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of site pollutant remediation, and in particular to a self-identifying slow-release remediation material for light non-aqueous phase pollutants, and a preparation method and application thereof. Background Art

[0002] Petroleum hydrocarbons are mainly composed of chain alkanes, cycloalkanes and aromatics. During the production, storage, transportation and use of the petrochemical industry, petrochemical raw materials, intermediate products and products will enter the soil and groundwater of the site through "leakage", causing soil and groundwater pollution and forming light non-aqueous phase oil layers (LNAPL) in the strata. Light non-aqueous phase pollutants are widely present in petrochemical enterprises. Their density is lower than that of groundwater. During the infiltration process, they are mainly present in the low permeability area of ​​the vadose zone or the groundwater level fluctuation area. The LNAPL phase contaminated layer contains a large number of high-concentration, highly toxic and poorly water-soluble organic pollutants, and the migration and diffusion process can cause the expansion of the oil pollution plume in the water. It is a high-risk pollution source for soil and groundwater, and can also produce volatilization to form organic vapor intrusion, which is extremely harmful to human health and the ecological environment. Therefore, it is of great significance to adopt targeted technologies and materials to achieve timely and efficient removal and diffusion control of LNAPL.

[0003] The existing LNAPL remediation treatment mainly includes in-situ chemical oxidation, in-situ extraction treatment and microbial degradation, and there are engineering application cases both at home and abroad. In-situ chemical oxidation technology adopts the method of injecting the remediation agent into the LNAPL contaminated stratum under pressure, and through the oxidation reaction between the agent and the pollutant, the LNAPL phase and the oil pollutants in the water are purified and removed. For example, patent application CN106269823B and others have published a method for remediating soil contaminated by high concentrations of organic matter. The core of this technology is the injected oxidizing agent, but the organic matter in the soil will also consume the oxidizing agent, and the LNAPL pollutants will fluctuate with the groundwater. If the injected agent fails to contact the pollutants, the multi-substance component system in the soil will gradually lose its oxidizing ability, and the effective utilization rate is low. In-situ extraction treatment technology usually uses a power pump device to generate negative pressure to extract the LNAPL phase and contaminated groundwater to the ground for purification, such as patent application CN110255638A and patent application CN111137941A. This type of extraction treatment technology is not very targeted, and there is often a LNAPL tailing rebound phenomenon after repair, and the pollutants after extraction still need to be purified, and the overall operating cost is high. Microbial degradation technology is mainly aimed at low-concentration petroleum hydrocarbon pollutants in soil and groundwater, such as the bioremediation composition technology with delayed release materials for removing hydrocarbons from a contaminated environment published in patent application CN107399830A, etc., which uses a variety of bioremediation materials to achieve the degradation of petroleum hydrocarbons. For high-concentration LNAPL phase pollutants, they are highly toxic and low in biodegradability, and the degradation efficiency of petroleum hydrocarbons is low, making it difficult to efficiently complete the degradation and removal of LNAPL.

[0004] At present, the remediation materials involved in the above-mentioned in-situ chemical oxidation, in-situ extraction treatment and microbial degradation mainly include chemical oxidants, surface solubilizers and biostimulants. For example, patent application CN114904906A discloses a non-aqueous phase liquid pollutant remediation agent and its preparation method and application, which mainly adopts ion pair oxidants soluble in non-aqueous phase composed of inorganic oxidants such as quaternary ammonium salts and persulfates, but the oxidation process cannot identify the LNAPL phase, and the remediation target lacks specificity. It will be consumed by environmental components such as soil organic matter, and it is difficult to fully realize effective utilization; patent application CN104773766A discloses soybean oil-coated nano-iron slurry groundwater pollution remediation reagents and their preparation methods, which mainly adopt soybean oil embedding to protect the antioxidant capacity of nano-iron in the air and improve its migration performance in underground porous bodies, and do not control its release ability; in the in-situ extraction treatment technology, surface solubilizers can also be injected to promote the effect, such as patent application Please refer to CN111215000A for a surfactant used for treating non-aqueous phase pollutants in soil and groundwater. Its main function is to perform elution and solubilization during in-situ extraction treatment, and it cannot achieve the purification and removal of LNAPL phase pollutants. Publication No. CN110759319A discloses a slow-release nano calcium peroxide material and its preparation and method for removing chlorinated hydrocarbons and / or benzene series in groundwater. The material can achieve sustained release of the agent through structural design. Its main function is to stimulate microbial metabolism by increasing the electron donor level through calcium peroxide, thereby repairing low-concentration soil and groundwater organic pollutants. Since calcium peroxide needs to react with water, resulting in limited mass transfer effect, and LNAPL is highly toxic, the material is not effective for LNAPL phases and high-concentration pollutants.

[0005] The existing groundwater in-situ chemical oxidation, in-situ extraction treatment and microbial degradation and remediation technologies and materials can basically meet the degradation and removal of water-soluble petroleum hydrocarbon pollutants in groundwater. However, there are still many problems in the remediation and removal capabilities for the occurrence characteristics of water-insoluble NAPL phase pollutants, such as tailing rebound and low effective utilization rate. Moreover, LNAPL will fluctuate up and down or migrate horizontally with the groundwater flow field and water level. This rebound precipitation and fluctuating migration is also hidden and difficult to detect and treat in the first time. In addition, the existing technologies and agents lack efficient identification selectivity. Therefore, it is urgent to develop new targeted removal materials. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of tailing rebound, low effective utilization rate, low recognition, etc. in the existing remediation technology, and to provide a self-identifying slow-release remediation material for light non-aqueous phase pollutants and its preparation method and application. The self-identifying slow-release remediation material for light non-aqueous phase pollutants described in the present invention is a granular material with a multi-layer core-shell structure. After being injected into the soil and groundwater of the site, when the migration or tailing rebound of the pollutants leads to the appearance of LNAPL phase pollutants, the self-identifying slow-release remediation material for light non-aqueous phase pollutants can self-identify and start to release the internal remediation agent material, thereby achieving the purification and removal of the LNAPL phase and oil in the water of the contaminated stratum.

[0007] In order to achieve the above-mentioned object, the present invention provides a self-recognition and slow-release repair material for light non-aqueous phase pollutants, wherein the self-recognition and slow-release repair material has a multiple core-shell structure, wherein the multiple core-shell structure has a core, a first coating layer, and a second coating layer sequentially distributed from the inside to the outside;

[0008] wherein the core contains a repair component;

[0009] The first coating layer has pores, and the first coating layer contains a thermosetting resin;

[0010] The second coating layer contains a fat-soluble material.

[0011] Preferably, the inner core has a diameter of 250-350 μm.

[0012] Preferably, the repair component contains an oxidative repair agent and an optional auxiliary agent;

[0013] Preferably, the oxidation repair agent is selected from one or more of persulfate, potassium permanganate and peroxide;

[0014] Preferably, the auxiliary agent is selected from one or more of a catalyst, a pH regulator and a solubilizing agent.

[0015] Preferably, the catalyst is selected from one or more of ferrous sulfate, manganese oxide composite materials and nano iron materials;

[0016] Preferably, the pH regulator is selected from one or more of ferric chloride, ammonium chloride and aluminum chloride;

[0017] Preferably, the solubilizing agent is selected from one or more of triethanolamine soap, polysorbate and rhamnolipid.

[0018] Preferably, the pore size of the first coating layer is 0.1-10 μm;

[0019] Preferably, the porosity of the first coating layer is 50-70%.

[0020] Preferably, the thickness of the first coating layer is 10-100 μm.

[0021] Preferably, the thermosetting resin is selected from one or more of medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin and polymethyl silicone resin.

[0022] Preferably, the thickness of the second coating layer is 10-100 μm.

[0023] Preferably, the fat-soluble material is selected from one or more of fatty acids, paraffin and glycerol;

[0024] Preferably, the fatty acid is selected from C16-C20 fatty acids.

[0025] The second aspect of the present invention provides a method for preparing a self-identifying slow-release repair material for light non-aqueous phase pollutants, the method comprising the following steps:

[0026] S1: mixing the repair component with the binder, and then granulating to obtain the core;

[0027] S2: mixing a thermosetting resin and ethanol to obtain a first coating solution, and coating the inner core with the first coating solution to form a first coating layer on the inner core surface;

[0028] S3: heating the fat-soluble material to obtain a second coating solution, and using the second coating solution to coat the material obtained in step S2 to form a second coating layer on the surface of the first coating layer.

[0029] Preferably, the repair component contains an oxidative repair agent and an optional auxiliary agent;

[0030] Preferably, the oxidation repair agent is selected from one or more of persulfate, potassium permanganate and peroxide;

[0031] The auxiliary agent is selected from one or more of a catalyst, a pH regulator and a solubilizing agent.

[0032] Preferably, in step S1, the weight ratio of the repair component to the adhesive is 5-9:1;

[0033] Preferably, the binder is selected from one or more of potassium silicate, phosphate, aluminate, inorganic cement and diatomaceous earth.

[0034] Preferably, the inner core has a diameter of 250-350 μm.

[0035] Preferably, in step S2, the volume ratio of the thermosetting resin to ethanol is 1-3:1;

[0036] Preferably, the volume ratio of the kernel to the first coating liquid is 1-3:1;

[0037] Preferably, the thermosetting resin is selected from one or more of medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin and polymethyl silicone resin.

[0038] Preferably, the specific process of step S2 includes:

[0039] A thermosetting resin and ethanol are mixed to obtain a first coating solution, the kernels are placed in a preheated fluidized bed coater, and then the first coating solution is sprayed into the kernels for coating, followed by drying;

[0040] Preferably, the drying temperature is 70-90° C. and the drying time is 1-2 h.

[0041] Preferably, in step S2, the thickness of the first coating layer is 10-100 μm;

[0042] Preferably, the pore size of the first coating layer is 0.1-10 μm;

[0043] Preferably, the porosity of the first coating layer is 50-70%;

[0044] Preferably, in step S3, the fat-soluble material is selected from one or more of fatty acids, paraffin and glycerol;

[0045] Preferably, the fatty acid is selected from C16-C20 fatty acids.

[0046] Preferably, in step S3, the volume ratio of the material obtained in step (2) to the amount of the second coating liquid is 2-5:1.

[0047] Preferably, in step S3, the thickness of the second coating layer is 10-100 μm.

[0048] Preferably, the specific process of step S3 includes:

[0049] The fat-soluble material is heated to obtain a second coating liquid, the material obtained in step S2 is placed in a preheated fluidized bed coater, and then the second coating liquid is sprayed into the coating machine for coating, followed by drying;

[0050] Preferably, the drying temperature is 30-40° C. and the drying time is 1-3 h.

[0051] The third aspect of the present invention provides a self-identifying slow-release repair material for light non-aqueous pollutants prepared by the method described above.

[0052] The fourth aspect of the present invention provides the use of the above-mentioned self-identifying slow-release remediation material for light non-aqueous phase pollutants in the remediation of light non-aqueous phase pollutants.

[0053] Compared with the prior art, the self-identifying slow-release repair material for light non-aqueous phase pollutants of the present invention has the following beneficial effects:

[0054] 1. The self-identifying slow-release remediation material for light non-aqueous phase pollutants of the present invention has the function of selectively identifying LNAPL phase pollutants. When the second coating layer encounters LNAPL phase pollutants or high-concentration oil in water (high oil content in the water phase), it can self-dissolve, thereby starting the release of LNAPL phase pollutant remediation agent materials, and realizing timely and efficient purification and removal of the LNAPL phase.

[0055] 2. The first coating layer of the self-identifying slow-release repair material for light non-aqueous phase pollutants described in the present invention not only has the function of controlling the release rate of the repair agent, but also is composed of a hydrophobic and lipophilic thermosetting resin, which can improve the affinity and adhesion to organic pollutants and enhance the directional removal ability of LNAPL phases and oil pollutants in water.

[0056] 3. The self-identifying slow-release remediation material for light non-aqueous phase pollutants described in the present invention can be combined with in-situ extraction and treatment technology to solve the tailing rebound problem of the extracted and treated LNAPL phase pollutants after injection into the ground. It can also be directly injected into the target formation in sufficient quantity to solve the problem of LNAPL pollutants fluctuating with the groundwater level, thereby improving the LNAPL remediation efficiency.

[0057] 4. The self-identifying slow-release remediation material for light non-aqueous phase pollutants described in the present invention can selectively identify LNAPL phase pollutants, avoid the consumption of remediation materials by the multi-component system of soil and groundwater itself, reduce the injection amount of remediation agent materials, and effectively improve the utilization rate of agents. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 It is a schematic structural diagram of a self-identifying and sustained-release repair material for light non-aqueous pollutants according to an embodiment of the present invention.

[0059] Description of Reference Numerals

[0060] 1 Second coating layer 2 First coating layer

[0061] 3 cores DETAILED DESCRIPTION

[0062] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0063] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0064] The first aspect of the present invention provides a self-identifying slow-release repair material for light non-aqueous phase pollutants, Figure 1 The self-recognition sustained-release repair material has a multiple core-shell structure, and the multiple core-shell structure has a core 3, a first coating layer 2, and a second coating layer 1 distributed sequentially from the inside to the outside;

[0065] Wherein, the core 3 contains a repair component;

[0066] The first coating layer 2 has pores, and the first coating layer 2 contains a thermosetting resin;

[0067] The second coating layer 1 contains a fat-soluble material.

[0068] In a preferred embodiment, the core 3 further contains a binder, which is helpful to maintain the stability of the shape and structure of the core 3.

[0069] More preferably, the diameter of the inner core 3 is 250-350 μm.

[0070] In a preferred embodiment, the repair component contains an oxidation repair agent and optionally an auxiliary agent.

[0071] Further preferably, the oxidation repair agent is selected from one or more of persulfate, potassium permanganate and peroxide.

[0072] More preferably, the auxiliary agent is selected from one or more of a catalyst, a pH regulator and a solubilizing agent. The auxiliary agent is used to enhance the repair effect of the repair material.

[0073] Further preferably, the catalyst can be selected from one or more of ferrous sulfate, manganese oxide composite materials and nano iron materials;

[0074] Further preferably, the pH adjuster can be selected from one or more of ferric chloride, ammonium chloride and aluminum chloride;

[0075] More preferably, the solubilizing agent may be selected from one or more of triethanolamine soap, polysorbate and rhamnolipid.

[0076] In a specific embodiment, when the oxidation repair agent is selected from persulfate, the auxiliary agent is selected from catalysts and dissolution promoters.

[0077] In a specific embodiment, when the oxidation repair agent is selected from potassium permanganate, the auxiliary agent is selected from a pH regulator and a dissolution promoter.

[0078] According to a preferred embodiment of the present invention, when the repair component contains an oxidative repair agent and an auxiliary agent, the weight ratio of the oxidative repair agent to the auxiliary agent is 1-4:1; specifically, it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.

[0079] In a preferred embodiment, the pore size of the first coating layer 2 is 0.1-10 μm.

[0080] In the present invention, the pore size of the first coating layer 2 refers to the average pore size, which can be measured by the BET method.

[0081] In a preferred embodiment, the porosity of the first coating layer 2 is 50-70%; specifically, it can be 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 62%, 64%, 66%, 68% or 70%.

[0082] In a preferred embodiment, the thickness of the first coating layer 2 is 10-100 μm; specifically, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 95 μm or 100 μm.

[0083] In a preferred embodiment, the thermosetting resin is selected from one or more of medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin and polymethyl silicone resin.

[0084] In a preferred embodiment, the thickness of the second coating layer 1 is 10-100 μm, specifically 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm.

[0085] In the present invention, the first coating layer 2 can control the release rate of the repair agent and improve the utilization efficiency of the agent. At the same time, the layer is composed of a hydrophobic and lipophilic thermosetting resin, which has the function of promoting the directional removal of the LNAPL oil phase and the oil in the water, thereby improving the targeted repair efficiency. By reasonably controlling the pore size and porosity of the first coating layer 2, the release rate of the repair agent material can be controlled at the molecular level.

[0086] In a preferred embodiment, the fat-soluble material is selected from one or more of fatty acids, paraffin and glycerol.

[0087] Further preferably, the fatty acid is selected from C16-C20 fatty acids.

[0088] In a specific embodiment, the fatty acid is a C18 fatty acid.

[0089] In the present invention, when the second coating layer 1 contacts the LNAPL phase or high-concentration oil pollutants in water, the second coating layer 1 may dissolve, thereby self-identifying and starting to release the LNAPL phase pollutant remediation agent in the body, and the effective self-identifying and dissolving time in the LNAPL phase pollutants is 2-5 minutes.

[0090] The self-identifying slow-release remediation material for light non-aqueous phase pollutants described in the present invention can be combined with in-situ extraction treatment technology and injected into the ground in the later stage of extraction treatment. When LNAPL phase pollutants rebound and precipitate again, the self-identifying slow-release remediation material described in the present invention can perform selective identification and self-dissolution identification of the shell, thereby initiating the release of LNAPL phase pollutant remediation agent materials and solving the tailing rebound problem of LNAPL phase pollutants in the extraction treatment.

[0091] The second aspect of the present invention provides a method for preparing a self-identifying slow-release repair material for light non-aqueous phase pollutants, the method comprising the following steps:

[0092] S1: mixing the repair component with the binder, and then granulating to obtain the core;

[0093] S2: mixing a thermosetting resin and ethanol to obtain a first coating solution, and coating the inner core with the first coating solution to form a first coating layer on the inner core surface;

[0094] S3: heating the fat-soluble material to obtain a second coating solution, and using the second coating solution to coat the material obtained in step S2 to form a second coating layer on the surface of the first coating layer.

[0095] In a preferred embodiment, the repair component contains an oxidation repair agent and optionally an auxiliary agent.

[0096] Further preferably, the oxidation repair agent is selected from one or more of persulfate, potassium permanganate and peroxide.

[0097] In a preferred embodiment, the auxiliary agent is selected from one or more of a catalyst, a pH adjuster and a solubilizing agent.

[0098] In a specific embodiment, the catalyst can be a transition-activated metal compound, for example, it can be selected from one or more of ferrous sulfate, manganese oxide composite materials and nano-iron materials; the pH adjuster can be selected from one or more of ferric chloride, ammonium chloride and aluminum chloride; the solubilizing agent can be selected from one or more of triethanolamine soap, polysorbate and rhamnolipid.

[0099] In a preferred embodiment, when the repair component contains an oxidative repair agent and an auxiliary agent, the weight ratio of the oxidative repair agent to the auxiliary agent is 1-4:1; specifically, it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.

[0100] In a preferred embodiment, in step S1, the weight ratio of the repair component to the adhesive is 5-9:1; specifically, it can be 5:1, 6:1, 7:1, 8:1 or 9:1.

[0101] Further preferably, the binder is selected from one or more of potassium silicate, phosphate, aluminate, inorganic cement and diatomaceous earth.

[0102] In a preferred embodiment, in step S1, the granulation can be carried out in a conventional device in the art, which can form a mixture of the repair component and the binder, for example, a mixing pelletizer can be used.

[0103] Preferably, the diameter of the inner core is 250-350 μm; specifically, the diameter of the inner core may be 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm or 350 μm.

[0104] In the method of the present invention, in step S2, the kernel obtained in step S1 is coated with a first coating solution to form a first coating layer on the surface of the kernel. The first coating layer can control the release rate of the repair agent and improve the utilization efficiency of the agent.

[0105] In the method of the present invention, in order to further improve the sustained release performance of the self-recognizing sustained release repair material, the amount of thermosetting resin and ethanol can be reasonably controlled. In a preferred embodiment, in step S2, the volume ratio of the amount of thermosetting resin and ethanol is 1-3:1.

[0106] In a preferred embodiment, in step S2, the volume ratio of the inner core to the first coating liquid is 1-3:1; specifically, it can be 1:1, 1.5:1, 2:1, 2.5:1 or 3:1.

[0107] In a preferred embodiment, the thermosetting resin is selected from one or more of medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin and polymethyl silicone resin.

[0108] In a preferred embodiment, the specific process of step S2 includes:

[0109] A thermosetting resin and ethanol are mixed to obtain a first coating solution, the kernel is placed in a preheated fluidized bed coating machine, and then the first coating solution is sprayed into the kernel for coating, followed by drying.

[0110] In a preferred embodiment, in step S2, the preheating temperature is 40-60°C; specifically, it can be 40°C, 45°C, 50°C, 55°C or 60°C.

[0111] In a preferred embodiment, in step S2, the drying temperature is 70-90°C and the drying time is 1-2 hours. Specifically, the drying temperature may be 70°C, 75°C, 80°C, 85°C or 90°C.

[0112] In a preferred embodiment, the coating process in step S2 can be performed in a fluidized bed coater.

[0113] In the method of the present invention, in order to further improve the sustained release performance and repair performance of the self-identifying sustained release repair material, the thickness, pore size and porosity of the obtained first coating layer can be reasonably controlled. In a preferred embodiment, the thickness of the first coating layer is 10-100 μm; specifically, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 95 μm or 100 μm. The pore size of the first coating layer is 0.1-10 μm; more preferably, it is 6-8 μm; the porosity of the first coating layer is 50-70%; more preferably, it is 55-65%.

[0114] In the method described in the present invention, in step S2, a mixture of thermosetting resin and ethanol is used as the coating liquid, and the thermosetting resin is used as the main component of the first coating layer 2, which has the function of promoting the directional removal of LNAPL oil phase and oil in water, thereby improving the targeted repair efficiency; ethanol evaporates during the drying process so that the first coating layer has a certain amount of pores, further improving the sustained-release performance of the repair material.

[0115] In the method of the present invention, in step S3, the material obtained in step S2 (i.e., the kernel coated with the first coating layer) is coated with the second coating liquid, so that a second coating layer is formed on the surface of the first coating layer. When the second coating layer contacts the LNAPL phase or the oil pollutant in the high concentration water, it can be dissolved, thereby self-identifying and starting to release the LNAPL phase pollutant remediation agent in the body.

[0116] In a preferred embodiment, in step S3, the fat-soluble material is selected from one or more of fatty acids, paraffin and glycerol.

[0117] Further preferably, the fatty acid is selected from C16-C20 fatty acids.

[0118] In a preferred embodiment, in step S3, the volume ratio of the material obtained in step S2 to the amount of the second coating solution is 2-5:1; specifically, it can be 2:1, 3:1, 4:1 or 5:1.

[0119] In the method of the present invention, in order to further improve the recognition ability of the second coating layer to LNAPL phase pollutants and enable rapid dissolution, the thickness of the second coating layer can be reasonably controlled. In a preferred embodiment, in step S3, the thickness of the second coating layer is 10-100 μm; specifically, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm.

[0120] In a preferred embodiment, the specific process of step S3 includes:

[0121] The fat-soluble material is heated to obtain a second coating liquid, the material obtained in step S2 is placed in a preheated fluidized bed coater, and then the second coating liquid is sprayed into the coating machine for coating, followed by drying.

[0122] In a preferred embodiment, in step S3, the heating temperature is 80-90°C; specifically, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C.

[0123] In a preferred embodiment, in step S3, the preheating temperature is 40-60°C; specifically, it can be 40°C, 45°C, 50°C, 55°C or 60°C.

[0124] In a preferred embodiment, in step S3, the drying temperature is 30-40° C. and the drying time is 1-3 h.

[0125] In a preferred embodiment, the coating process in step S3 can be performed in a fluidized bed coater.

[0126] The third aspect of the present invention provides a self-recognizing sustained-release repair material prepared by the method described above.

[0127] The fourth aspect of the present invention provides the use of the self-identifying slow-release repair material described above in the repair of light non-aqueous phase pollutants.

[0128] The self-identifying slow-release repair material of the present invention can adopt in-situ chemical oxidation injection technology, and the material can be injected into LNAPL contaminated and fluctuating formations through pressure difference to achieve purification and removal of LNAPL pollutants; it can also be used in conjunction with in-situ extraction and treatment technology, and extraction is used in the early stage of LNAPL and oil in water repair, and the self-identifying slow-release repair material is subsequently injected to achieve the removal of rebound precipitated LNAPL phase pollutants.

[0129] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0130] Unless otherwise specified, the reagents used in the following examples and comparative examples are all commercially available products.

[0131] Example 1

[0132] S1: The repair component and the binder (phosphate adhesive) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, the granulation speed is 180rpm, the granulation temperature is 30°C, and the granulation time is 30min, to obtain a core with a diameter of 306μm; wherein the repair component is composed of an oxidative repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent is selected from a catalyst (ferrous sulfate) and a solubilizing agent (triethanolamine soap), and the weight ratio of the oxidative repair agent to the auxiliary agent is 2.4:1;

[0133] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 80°C for drying for 1.5 hours, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2:1; the first coating layer has a thickness of 88 μm, a porosity of about 55%, and a pore size of about 6 μm;

[0134] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 2 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the formed second coating layer is 42 μm.

[0135] Example 2

[0136] S1: The repair component and the binder (phosphate adhesive) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 290 μm; wherein the repair component is composed of an oxidative repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent is selected from a catalyst (ferrous sulfate) and a solubilizing agent (triethanolamine soap), and the weight ratio of the oxidative repair agent to the auxiliary agent is 1.43:1;

[0137] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed in a volume ratio of 1.86:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 80°C for drying for 1.5 hours, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2:1; the first coating layer has a thickness of 85 μm, a porosity of about 55%, and a pore size of about 6 μm;

[0138] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 2 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the formed second coating layer is 40 μm.

[0139] Example 3

[0140] S1: The repair component and the binder (phosphate adhesive) are mixed in a weight ratio of 9:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 316 μm; wherein the repair component is composed of an oxidative repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent is selected from a catalyst (ferrous sulfate) and a solubilizing agent (triethanolamine soap), and the weight ratio of the oxidative repair agent to the auxiliary agent is 3.5:1;

[0141] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 85°C for drying for 1.5 hours, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2:1; the thickness of the formed first coating layer is 86 μm, the porosity is about 55%, and the pore size is about 6 μm;

[0142] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 2.5 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the formed second coating layer is 40 μm.

[0143] Example 4

[0144] S1: The repair component and the binder (phosphate adhesive) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 310 μm; wherein the repair component is composed of an oxidative repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent is selected from a catalyst (ferrous sulfate) and a solubilizing agent (triethanolamine soap), and the weight ratio of the oxidative repair agent to the auxiliary agent is 2.4:1;

[0145] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.22:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 90°C for drying for 1 hour, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2.5:1; the thickness of the formed first coating layer is 72 μm, the porosity is about 61%, and the pore size is about 7 μm;

[0146] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 2 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 4:1, and the thickness of the formed second coating layer is 28 μm.

[0147] Example 5

[0148] S1: The repair component and the binder (phosphate adhesive) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 300 μm; wherein the repair component is composed of an oxidative repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent is selected from a catalyst (ferrous sulfate) and a solubilizing agent (triethanolamine soap), and the weight ratio of the oxidative repair agent to the auxiliary agent is 2.4:1;

[0149] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.22:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 80°C for drying for 1.5 hours, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2.5:1; the first coating layer has a thickness of 71 μm, a porosity of about 62%, and a pore size of about 7 μm;

[0150] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 2 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3.5:1, and the thickness of the formed second coating layer is 33 μm.

[0151] Example 6

[0152] S1: The repair component and the binder (potassium silicate binder) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 310 μm; wherein the repair component is composed of an oxidative repair agent (potassium permanganate) and an auxiliary agent, the auxiliary agent is selected from a pH regulator (ferric chloride) and a solubilizing agent (polysorbate), and the weight ratio of the oxidative repair agent to the auxiliary agent is 2.4:1;

[0153] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 85°C for drying for 1 hour, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2:1; the thickness of the formed first coating layer is 91 μm, the porosity is about 56%, and the pore size is about 7 μm;

[0154] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 2 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the formed second coating layer is 40 μm.

[0155] Example 7

[0156] S1: The repair component and the binder (potassium silicate binder) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 305 μm; wherein the repair component is composed of an oxidative repair agent (potassium permanganate) and an auxiliary agent, the auxiliary agent is selected from a pH regulator (ferric chloride) and a solubilizing agent (polysorbate), and the weight ratio of the oxidative repair agent to the auxiliary agent is 1.43:1;

[0157] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 80°C for drying for 1.5 hours, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2:1; the thickness of the formed first coating layer is 90 μm, the porosity is about 56%, and the pore size is about 7 μm;

[0158] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 40°C air for drying for 2 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the formed second coating layer is 40 μm.

[0159] Example 8

[0160] S1: The repair component and the binder (potassium silicate binder) are mixed in a weight ratio of 9:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 290 μm; wherein the repair component is composed of an oxidative repair agent (potassium permanganate) and an auxiliary agent, the auxiliary agent is selected from a pH regulator (ferric chloride) and a solubilizing agent (polysorbate), and the weight ratio of the oxidative repair agent to the auxiliary agent is 3.5:1;

[0161] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 85°C for drying for 1.5 hours, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2:1; the first coating layer has a thickness of 90 μm, a porosity of about 50%, and a pore size of about 7 μm;

[0162] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 2 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the formed second coating layer is 40 μm.

[0163] Example 9

[0164] S1: The repair component and the binder (potassium silicate binder) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 308 μm; wherein the repair component is composed of an oxidative repair agent (potassium permanganate) and an auxiliary agent, the auxiliary agent is selected from a pH regulator (ferric chloride) and a solubilizing agent (polysorbate), and the weight ratio of the oxidative repair agent to the auxiliary agent is 2.4:1;

[0165] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.22:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 85°C for drying for 1.5 hours, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2.5:1; the first coating layer has a thickness of 70 μm, a porosity of about 60%, and a pore size of about 7 μm;

[0166] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 2.5 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the formed second coating layer is 45 μm.

[0167] Example 10

[0168] S1: The repair component and the binder (potassium silicate binder) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 295 μm; wherein the repair component is composed of an oxidative repair agent (potassium permanganate) and an auxiliary agent, the auxiliary agent is selected from a pH regulator (ferric chloride) and a solubilizing agent (polysorbate), and the weight ratio of the oxidative repair agent to the auxiliary agent is 2.4:1;

[0169] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.22:1 to obtain a first coating solution, the kernel is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with hot air at 90°C for drying for 1.5 hours, to form a first coating layer on the surface of the kernel; wherein the volume ratio of the kernel to the first coating solution is 2.5:1; the first coating layer has a thickness of 70 μm, a porosity of about 63%, and a pore size of about 7 μm;

[0170] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution, the material obtained in step S2 is placed in a fluidized bed coater preheated to 45°C, and then the second coating solution is sprayed for coating, followed by spraying with 35°C air for drying for 3 hours, to form a second coating layer on the surface of the first coating layer; wherein the volume ratio of the material obtained in step S2 to the second coating solution is 3.5:1, and the thickness of the formed second coating layer is 30 μm.

[0171] Comparative Example 1

[0172] S1: The repair component and the binder (phosphate adhesive) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of 300 μm; wherein the repair component is composed of an oxidative repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent is selected from a catalyst (ferrous sulfate) and a solubilizing agent (triethanolamine soap), and the weight ratio of the oxidative repair agent to the auxiliary agent is 2.4:1;

[0173] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed in a volume ratio of 1.86:1 to obtain a first coating solution, the inner core is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with 80°C hot air for drying for 1.5 hours to form a first coating layer on the surface of the inner core; wherein the volume ratio of the inner core to the first coating solution is 2:1; the thickness of the formed first coating layer is 85 μm, the porosity is about 56%, and the pore size is about 7 μm.

[0174] Comparative Example 2

[0175] S1: The repair component and the binder (potassium silicate binder) are mixed in a weight ratio of 5.67:1, and then granulated in a mixing pelletizer, with a granulation speed of 180 rpm, a granulation temperature of 30°C, and a granulation time of 30 min to obtain a core with a diameter of about 305 μm; wherein the repair component is composed of an oxidative repair agent (potassium permanganate) and an auxiliary agent, the auxiliary agent is selected from a pH regulator (ferric chloride) and a solubilizing agent (polysorbate), and the weight ratio of the oxidative repair agent to the auxiliary agent is 2.4:1;

[0176] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed in a volume ratio of 1.86:1 to obtain a first coating solution, the inner core is placed in a fluidized bed coater preheated to 50°C, and then the first coating solution is sprayed for coating, followed by spraying with 85°C hot air for drying for 1 hour, to form a first coating layer on the surface of the inner core; wherein the volume ratio of the inner core to the first coating solution is 2:1; the thickness of the formed first coating layer is 90 μm, the porosity is about 56%, and the pore size is about 7 μm.

[0177] Test Case

[0178] 1. The sustained release performance and LNAPL phase pollutant removal capacity of the products obtained in Examples 1-5 and Comparative Example 1 were tested. The test process is as follows:

[0179] In a 1000mL beaker, add 50g of uncontaminated soil and 500mL of groundwater, and then add 5g of the sample to be tested into the beaker. The sample to be tested floats on the water surface, and the sulfur content in the water is determined by the combustion neutralization method at 1h, 4h, 12h, and 20h, respectively. Then, 1mL of petroleum ether is added at 24h, and the sulfur content in the water is determined by the combustion neutralization method at 25h and 26h. The petroleum ether content in the water is determined by extraction at 48h, and the removal rate of LNAPL phase pollutants (petroleum ether) is calculated.

[0180] The test results are shown in Table 1. Compared with the comparative example, before the petroleum ether LNAPL phase pollutants were added, the oxidative remediation agent in the product obtained in the embodiment was not released. After the petroleum ether LNAPL phase pollutants were added, the product obtained in the embodiment self-identified and dissolved its shell, and the sulfur-containing effective remediation components were quickly released. The pollutant removal rate was ≥87.2% after detection. The sulfur-containing remediation components of the product obtained in the comparative example were naturally released after addition, and were consumed by the reducing components of the soil and groundwater themselves in the early stage. After the pollutants were added, the removal rate was about 41.6%, and the effectiveness was significantly lower.

[0181] Table 1

[0182]

[0183] 2. The sustained release performance and LNAPL phase pollutant removal capacity of the products obtained in Examples 6-10 and Comparative Example 2 were tested. The test process is as follows:

[0184] In a 1000mL beaker, add 50g of uncontaminated soil and 500mL of groundwater, add 5g of the sample to be tested into the beaker, dissolve the sample in water, and determine the manganese content in the water by atomic absorption spectrophotometry at 1h, 4h, 12h, and 20h, respectively. Then, add 1mL of petroleum ether at 24h, and continue to determine the manganese content in the water by atomic absorption spectrophotometry at 25h and 26h. Determine the petroleum ether content in the water by extraction at 48h, and calculate the LNAPL phase pollutant removal rate.

[0185] The test results are shown in Table 2. Compared with Comparative Example 2, before the petroleum ether LNAPL phase pollutants were added, the oxidative remediation agent in the products obtained in Examples 6-10 was not released. After the petroleum ether LNAPL phase pollutants were added, the products obtained in the Examples self-identified shell dissolution, and the manganese-containing effective remediation components were quickly released, and the pollutant removal rate was ≥85.6%; while the manganese-containing remediation components of the products in the comparative example were naturally released after addition, and were consumed by the reducing components of the soil and groundwater themselves in the early stage. After the pollutants were added, the removal rate was about 65.0%, and the effectiveness was significantly lower.

[0186] Table 2

[0187]

[0188] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A self-identifying and slow-release repair material for light non-aqueous phase pollutants, characterized in that: The self-recognition sustained-release repair material has a multiple core-shell structure, wherein the multiple core-shell structure has a core (3), a first coating layer (2) and a second coating layer (1) which are sequentially distributed from the inside to the outside; wherein the core (3) contains a repair component; The first coating layer (2) has pores, and the first coating layer (2) contains a thermosetting resin; The second coating layer (1) contains a fat-soluble material.

2. The self-identifying slow-release repair material for light non-aqueous phase pollutants according to claim 1, characterized in that: The diameter of the inner core (3) is 250-350 μm.

3. The self-identifying slow-release repair material for light non-aqueous phase pollutants according to claim 1 or 2, characterized in that: The repair component contains an oxidation repair agent and an optional auxiliary agent; Preferably, the oxidation repair agent is selected from one or more of persulfate, potassium permanganate and peroxide; Preferably, the auxiliary agent is selected from one or more of a catalyst, a pH regulator and a solubilizing agent; Preferably, the catalyst is selected from one or more of ferrous sulfate, manganese oxide composite materials and nano iron materials; Preferably, the pH regulator is selected from one or more of ferric chloride, ammonium chloride and aluminum chloride; Preferably, the solubilizing agent is selected from one or more of triethanolamine soap, polysorbate and rhamnolipid.

4. The self-identifying and slow-release repair material for light non-aqueous pollutants according to any one of claims 1 to 3, characterized in that: The pore size of the first coating layer (2) is 0.1-10 μm; Preferably, the porosity of the first coating layer (2) is 50-70%.

5. The self-identifying slow-release repair material for light non-aqueous phase pollutants according to claim 1 or 4, characterized in that: The thickness of the first coating layer (2) is 10-100 μm.

6. The self-identifying and slow-release repair material for light non-aqueous phase pollutants according to any one of claims 1 to 5, characterized in that: The thermosetting resin is selected from one or more of medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin and polymethyl silicone resin.

7. The self-identifying slow-release repair material for light non-aqueous phase pollutants according to claim 1, characterized in that: The thickness of the second coating layer (1) is 10-100 μm.

8. The self-identifying slow-release repair material for light non-aqueous phase pollutants according to claim 1 or 7, characterized in that: The fat-soluble material is selected from one or more of fatty acids, paraffin and glycerol; Preferably, the fatty acid is selected from C16-C20 fatty acids.

9. A method for preparing a self-identifying slow-release repair material for light non-aqueous phase pollutants, characterized in that: The method comprises the following steps: S1: mixing the repair component with the binder, and then granulating to obtain the core; S2: mixing a thermosetting resin and ethanol to obtain a first coating solution, and coating the inner core with the first coating solution to form a first coating layer on the inner core surface; S3: heating the fat-soluble material to obtain a second coating solution, and using the second coating solution to coat the material obtained in step S2 to form a second coating layer on the surface of the first coating layer.

10. The method according to claim 9, characterized in that The repair component contains an oxidation repair agent and an optional auxiliary agent; Preferably, the oxidation repair agent is selected from one or more of persulfate, potassium permanganate and peroxide; The auxiliary agent is selected from one or more of a catalyst, a pH regulator and a solubilizing agent.

11. The method according to claim 9 or 10, characterized in that: In step S1, the weight ratio of the repair component to the adhesive is 5-9:1; Preferably, the binder is selected from one or more of potassium silicate, phosphate, aluminate, inorganic cement and diatomaceous earth.

12. The method according to claim 9 or 11, characterized in that: In step S1, the diameter of the inner core is 250-350 μm.

13. The method according to any one of claims 9 to 12, characterized in that: In step S2, the volume ratio of the thermosetting resin to ethanol is 1-3:1; Preferably, the volume ratio of the kernel to the first coating liquid is 1-3:1; Preferably, the thermosetting resin is selected from one or more of medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin and polymethyl silicone resin.

14. The method according to claim 9 or 13, characterized in that: The specific process of step S2 includes: A thermosetting resin and ethanol are mixed to obtain a first coating solution, the kernels are placed in a preheated fluidized bed coater, and then the first coating solution is sprayed into the kernels for coating, followed by drying; Preferably, the drying temperature is 70-90° C. and the drying time is 1-2 h.

15. The method according to claim 9 or 14, characterized in that: In step S2, the thickness of the first coating layer is 10-100 μm; Preferably, the pore size of the first coating layer is 0.1-10 μm; Preferably, the porosity of the first coating layer is 50-70%.

16. The method according to any one of claims 9 to 15, characterized in that: In step S3, the fat-soluble material is selected from one or more of fatty acids, paraffin and glycerol; Preferably, the fatty acid is selected from C16-C20 fatty acids.

17. The method according to claim 9 or 16, characterized in that In step S3, the volume ratio of the material obtained in step S2 to the amount of the second coating liquid is 2-5:

1.

18. The method according to claim 9 or 16, characterized in that In step S3, the thickness of the second coating layer is 10-100 μm.

19. The method according to claim 9 or 17, characterized in that: The specific process of step S3 includes: The fat-soluble material is heated to obtain a second coating liquid, the material obtained in step S2 is placed in a preheated fluidized bed coater, and then the second coating liquid is sprayed into the coating machine for coating, followed by drying; Preferably, the drying temperature is 30-40° C. and the drying time is 1-3 h.

20. A self-identifying and slow-release repair material for light non-aqueous phase pollutants prepared by the method according to any one of claims 9 to 19.

21. Use of the self-identifying slow-release remediation material for light non-aqueous phase pollutants as described in any one of claims 1 to 8 and 20 in the remediation of light non-aqueous phase pollutants.

Citation Information

Patent Citations

  • Soybean oil coated nano-iron slurry groundwater pollution remediation reagent and preparation method thereof

    CN104773766A

  • A method for remediating soil contaminated with high concentrations of organic matter

    CN106269823B

  • Bioremediation composition with a time release material for removing hydrocarbons from contaminated environments

    CN107399830A

  • In-situ extraction processing system and method for polluted underground water containing non-aqueous phase liquid

    CN110255638A

  • Sustained-release nano-calcium peroxide materials, preparation thereof, and method for removing chlorohydrocarbon and / or benzene series from underground water through sustained-release nano-calcium peroxide materials

    CN110759319A